St-segment elevation myocardial infarction - Vogel, Birgit; Claessen, Bimmer E.; Arnold, Suzanne V.; Chan, Danny; Cohen, David J.; Giannitsis, Evangelos; Gibson, C. Michael; Goto, Shinya; Katus, Hugo; Kerneis, Mathieu; Kimura, Takeshi; Kunadian, Vijay; et al. (Nature reviews. Disease Primers, 2019)
ST-segment elevation myocardial infarction (STEMI) is an acute coronary syndrome in which transmural ischaemia (mostly caused by the formation of a thrombus on a ruptured atherosclerotic plaque) leads to cardiomyocyte death. STEMI is associated with considerable morbidity and mortality worldwide.